Structuring Management of the Post-Merger Integration Phase in the Buy-and-Build Model: The Case of a Private Network of Integrated Healthcare Entities - Nesterak, Janusz; Majkowski, Damian (Journal of Public Governance, 2023)
Objectives: In recent years, researchers have indicated a significant rising trend in the number of serial transactions carried out in the Buy-and-Build model. Simultaneously, managing the Post-Merger Integration (PMI) phase has not yet found much reflection in the investigations of researchers. The chosen subject of the research is related to activity which is focused on exploring the issue of proper management of the PMI phase in M&A projects. The article reviews the literature on the subject, supplementing it with a practical description of structuring the management of the PMI in the B&B model on the German market.Research Design & Methods: Information included in this article is mainly based on the analysis of the literature on the subject of PMI management, verified on the basis of publicly available data on the consolidation of the healthcare sector on Western European markets, supplemented with knowledge from the implementation of the PMI project on the German market. The conducted research was not verified on the basis of the realities of the Polish market and is not based on Polish literature of the subject.Findings: Structuring management of the PMI phase in the B&B model is unique and requires an individualised approach. Generic assumptions for the integration process are formulated and steering based on feedback mechanism from information provided by line managers responsible for a particular PMI. Observations coming from the practical case study show that there could be four generic stages in structuring the integration phase in the healthcare industry: (i) market context analysis; (ii) formulating the strategy including business planning and developing long-term financial projections; and (iii) developing the guidelines for the analysis of the entity subjected to acquisition and integration. Furthermore, proper management of the PMI phase should close within a strictly defined timeframe that is not longer than 120 days in order to avoid the degradation of the value resulting from acquisition.Implications / Recommendations: The perspective of private investors in the healthcare sector should be recognised by public managers. Investors from the private sector in Western countries, identifying the ineffectiveness of the public healthcare system, make attempts to recreate the architecture of the public healthcare system based on general and specialist clinics by acquiring private clinics and including them in a mutually-connected network. The upside from the investor's perspective that allows for generating a high rate of return on acquisition results from the effective management of the PMI phase due to, inter alia, building an IT infrastructure enabling the digitisation of patients' contact with medical institutions and building a product offer for companies providing access to private healthcare as an employee benefit.Contribution / Value Added: The main contribution of this paper is a practical description of structuring the management of the PMI in the B&B model on the foreign market of Western Europe based on the example of a serial acquisition of healthcare entities by a private equity investor. Furthermore, following recommendations by public managers operating in the healthcare sector – in particular those relating the need of digitalised contact between the patients, doctors, and clinics – could limit the negative impact for society, resulting from the extended time of access to medical care.